HUBUNGAN KECEPATAN LARI DAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK SISWA PUTRA KELAS X SMA NEGERI 2 BENGKALIS TAHUN 2016 - Hardiono, Ahmad; ', Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the observations result and information from PJOK teacher, the writer found several problems, namely a lack of running speed of students in doing the start and less limb muscle strength of students at the time of the repulsion that affected long jump test results of students. This reseach aims to know correlation of running speed and explosive power of legs with result of long jump squat style of male students on grade X in SMA Negeri 2 Bengkalis 2016. The form of this research is the correlation study, the population in this research are male students on grade X in SMA Negeri 2 Bengkalis 2016, and the sample in this research are male students on grade X in SMA Negeri 2 Bengkalis 2016 which consists of 81 students. To get the data, the writer used test of running 30 meters, standing broad jump, and long jump squat style. Then, the data were analyzed by using simple product moment correlation and continued with double correlations to get the relationship among these three variables. From the calculation of the first analysis between running speed (x1) and result of long jump squat style (y) where rtable at significant level Î± (0,05)=0,220, it means rresult (0,967) > rtable (0,220) as the result the hypothesis is accepted and there is a extremely strong correlation between the running speed and result of long jump squat style. The second analysis of the correlation between explosive power of legs (x2) and result of long jump squat styles(y), where rtable at a significant level Î± (0,05)=0,220 it means rresult (0,960)> rtable (0,220), hence, the hypothesis is accepted and there is a extremely strong correlation between explosive power of legs and result of long jump squat style. The third analysis correlation of running speed (x1) and explosive power of legs (x2) with the result of long jump squat style (y), where rtable at significant level Î± (0,05)=0,220 rresult (0,977)> rtable (0,220), meaning that the hypothesis is accepted and there is a extremely strong correlation of running speed and explosive power of legs with result of long jump squat styles.Keywords: Running Speed, Explosive Power of Legs, Result of Long jump Squat Styles